Field notes contributed by Matthew Kenne, summer 2000 - Kenne, Matthew C.et al (2000)
Summer report of birds found in northern Iowa contributed by Matthew Kenne. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed/flatbed